Traumatic Effects of the COVID-19 Outbreak in Middle School Students and Caregivers - Terzioğlu, Merve Aktaş (Psychiatry Investig, 2021)
OBJECTIVE: To investigate the traumatic effects of the COVID-19 pandemic on middle-school students and their parents. METHODS: This epidemiological cross-sectional study was conducted with middle-school students in Denizli. A questionnaire consisting of the IES-R, CRIES-13 and a sociodemographic data form was delivered online. A total of 1059 participants who fully completed the questionnaire were included for analysis. RESULTS: The IES-R total and subdimension scores and the CRIES-13 scores were found to be significantly higher in families with an income level of ≤2,500 TL. The CRIES-13 scores of children were found to be significantly higher in divorced families. No statistically significant difference was determined between the IES-R total and subdimension scores of the parents who were healthcare workers and the CRIES-13 scale scores of their children. CONCLUSION: A statistically significant, positive, moderate relationship was found between the IES-R scale total and subdimension scores of parents and the CRIES-13 scale scores of children. A low socioeconomic level was seen to increase the prevalence of anxiety in adults and adolescents. The children of divorced families were found to be at higher risk of PTSD. Successful management of mental health symptoms in parents will reflect positively on the mental health status of their children.